2016
DOI: 10.1186/s12862-016-0620-5
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate introns in nuclear genes of euglenids – are they a distinct type?

Abstract: BackgroundNuclear genes of euglenids contain two major types of introns: conventional spliceosomal and nonconventional introns. The latter are characterized by variable non-canonical borders, RNA secondary structure that brings intron ends together, and an unknown mechanism of removal. Some researchers also distinguish intermediate introns, which combine features of both types. They form a stable RNA secondary structure and are classified into two subtypes depending on whether they contain one (intermediate/no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 37 publications
(48 reference statements)
1
27
0
1
Order By: Relevance
“…7.5) (for details on Euglenoid introns see Milanowski et al 2014, 2016, andMcWaters andRussell, this volume). Overall gene lengths in the transcriptome are similar to those previously reported (Schantz and Schantz 1989;Jackson et al 2006;Levasseur et al 1994;Milanowski et al 2014Milanowski et al , 2016Canaday et al 2001), but are considerably shorter in the genome owing to truncation and fragmentation.…”
Section: The Tubulin and Calmodulin Genessupporting
confidence: 87%
“…7.5) (for details on Euglenoid introns see Milanowski et al 2014, 2016, andMcWaters andRussell, this volume). Overall gene lengths in the transcriptome are similar to those previously reported (Schantz and Schantz 1989;Jackson et al 2006;Levasseur et al 1994;Milanowski et al 2014Milanowski et al , 2016Canaday et al 2001), but are considerably shorter in the genome owing to truncation and fragmentation.…”
Section: The Tubulin and Calmodulin Genessupporting
confidence: 87%
“…Position of insertion of the group II intron in domain VI of the group III intron is indicated by the small box. Relative positions of branch point A nucleotides for both introns are indicated nucleotide in non-conventional introns has also been observed (Milanowski et al 2016) that perhaps affects splicing efficiency, thus explaining the frequent observation of non-conventional introns starting with the sequence 5′GT/C (i.e. spliceosomal-like) but also containing all other typical features of non-canonical introns.…”
Section: Nuclear-encoded Intronsmentioning
confidence: 89%
“…These could potentially be excised using components of both the spliceosome and trans-acting non-conventional intron splicing factors. Milanowski et al have recently examined the conservation of intron position and class in conserved nuclear genes in different Euglena species to shed light on such questions (Milanowski et al 2014(Milanowski et al , 2016. These studies have further refined the limited conserved sequence and structural features of non-conventional introns (as described above) and revealed that non-conventional intron gain/loss appears to occur much more frequently than observed for euglenid spliceosomal introns.…”
Section: Nuclear-encoded Intronsmentioning
confidence: 99%
See 2 more Smart Citations